Comparative vessel traits of Macaranga gigantea and Vatica dulitensis from Malaysian Borneo - Jotan P.; Colin Ruzelion Maycock; Burslem DFRP; Berhaman Ahmad; Both S. (2020)
Trade-offs in wood anatomical characteristics reflect different strategies used by trees to deal with water transport in response to variation in environmental conditions. To study vascular strategies for Bornean rainforest trees, we compared water transport-related anatomical characteristics in branch wood between the common tree species Vatica dulitensis (Dipterocarpaceae) from old-growth forest and the common pioneer tree species Macaranga gigantea (Euphorbiaceae) from selectively logged forest. We hypothesised that the vessel traits of the pioneer species would reflect the need to capture and transport resources to support its fast growth rate (resource-acquisitive strategy), while the species of the old-growth forest would display more conservative vessel traits (resource-conservative strategy). We found that M. gigantea had significantly greater vessel area, hydraulically weighted diameter, vessel area to number ratio, and potential hydraulic conductivity than V. dulitensis. These results suggest that vessel traits of the common old-growth species would ensure high hydraulic safety during occasional drought when soil moisture is limited, while the common species of selectively logged forest possesses an efficient water transport system but its vessels would confer lower hydraulic safety during drought conditions. These contrasting vascular strategies highlight the potential for divergent responses of species of Bornean forest trees to future climatic extremes.